2017
DOI: 10.1007/s11695-017-2596-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Severe Obesity on Healthcare Resource Utilisation in Spain

Abstract: Severe obesity significantly increases healthcare resource utilisation in Spain. The results shed light on the real magnitude of the burden of obesity in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
10
0
2
Order By: Relevance
“…Our results concerning the visiting rate of obese participants in the Emergency Department seems to confirm what has been described in other contexts. Obese individuals have a higher level of healthcare utilization [ 11 , 13 , 33 , 34 ]. A review from Kent et al analysed 75 studies and concluded that obese individuals had a mean increase of annual healthcare costs of 36%, compared to normal-weight individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results concerning the visiting rate of obese participants in the Emergency Department seems to confirm what has been described in other contexts. Obese individuals have a higher level of healthcare utilization [ 11 , 13 , 33 , 34 ]. A review from Kent et al analysed 75 studies and concluded that obese individuals had a mean increase of annual healthcare costs of 36%, compared to normal-weight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Bertakis et al did not find any differences in ED utilization between obese and normal-weight population. On the contrary, Espallardo et al found that ED utilization was higher for over class II obesity population but fail to take into account social variables throughout their analyses [ 25 , 34 ]. Other authors found a higher acute hospital admission rate and longer length-of-stay [ 26 , 33 ] but did not incorporate socio-economic status in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among high-income countries, people with obesity have ~30% more medical costs than people with normal weight ( 6 ). Similarly, adults living in Spain with a body mass index (BMI) ≥35 kg/m 2 use approximately twice as many primary care, home care, and psychology visits than adults with a normal BMI ( 7 ). In the United States (US), a country in which the healthcare system is based mainly on private insurance and out-of-pocket payments, the estimated yearly cost of medical visits, prescription drugs, or home care visits related to obesity is $149.4 billion ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a necessidade de tratamento especializado para esse público, com abordagem multidisciplinar, e a importância do apoio da rede familiar e dos profissionais são aspectos que aparecem no discurso de vários autores entre os selecionados [14][15][16][17][18]20,22,23,24 .…”
Section: A Atenção Primária à Saúde E Atividades Em Grupo No Tratamenunclassified
“…Espallardo et al 15 , Jennings et al 20 e Booth et al 21 chamam a atenção para o fato de que a utilização de recursos de saúde aumenta com a gravidade do excesso de peso e obesidade quando comparada com outros grupos de IMC (maior pro-babilidade de ser hospitalizado ou exigir outros serviços de saúde, como laboratórios e exames de imagens) e ressaltam a importância das intervenções da atenção primária no objetivo de reduzir o peso e os agravos de saúde desses indivíduos além do enfrentamento da obesidade.…”
Section: A Atenção Primária à Saúde E Atividades Em Grupo No Tratamenunclassified